2012
DOI: 10.1590/s0004-27302012000800003
|View full text |Cite
|
Sign up to set email alerts
|

Association of the rs7903146 single nucleotide polymorphism at the Transcription Factor 7-like 2 (TCF7L2) locus with type 2 diabetes in Brazilian subjects

Abstract: OBJECTIVE:To investigate the association of the T allele of the single nucleotide polymorphism (SNP) rs7903146 of TCF7L2 with the occurrence of T2D in a sample of subjects followed up at the Brasilia University Hospital. SUBJECTS AND METHODS: The SNP rs7903146 of TCF7L2 was genotyped by allele-specific PCR in 113 patients with known T2D and in 139 non-diabetic controls in Brasilia, Brazil. RESULTS:We found that the T allele of the SNP rs7903146 of TCF7L2 was significantly associated with T2D risk (odds ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
3
22
1
1
Order By: Relevance
“…First, we cannot rule out the possibility of population stratification bias when analyzing our samples, even though only white subjects were studied and both T2DM patients and non-diabetic subjects were recruited from the same hospital, thus reducing the risk of false-positive/negative associations due to this bias. Second, we did not perform a replication of the observed association in another sample from Southern Brazil, although our data is in agreement with the majority of studies performed in different populations (5)(6)(7)(8)31,(36)(37)(38)(39)(40) and also with another Brazilian study (23). Third, we only analyzed one SNP in the TCF7L2 gene.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…First, we cannot rule out the possibility of population stratification bias when analyzing our samples, even though only white subjects were studied and both T2DM patients and non-diabetic subjects were recruited from the same hospital, thus reducing the risk of false-positive/negative associations due to this bias. Second, we did not perform a replication of the observed association in another sample from Southern Brazil, although our data is in agreement with the majority of studies performed in different populations (5)(6)(7)(8)31,(36)(37)(38)(39)(40) and also with another Brazilian study (23). Third, we only analyzed one SNP in the TCF7L2 gene.…”
Section: Discussionsupporting
confidence: 45%
“…Barra and cols. (23) reported that the T/T genotype was significantly associated with T2DM risk (OR = 3.92, 95% CI 1.49-10.3 for the recessive model) in a small sample from the population of Brasilia, in the Central Western region of Brazil. Although they analyzed a sample of mixed ethnicity, the frequency of the T allele in their study was similar to that presented here.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, this polymorphism was found associated with diabetes in several works carried out in admixed populations from other Latin American countries (9,(23)(24)(25)28,29,31,32). However, Barros and cols.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, among Latin American countries there are only reports on the association of TCF7L2 polymorphisms and T2DM from Colombia (23), Brazil (24)(25)(26)(27)(28) and Mexico (9,(29)(30)(31)(32). Latin American populations are characterized by high socioeconomic and genetic heterogeneity with varying degrees of ancestral population proportions from country to country, thus more studies are needed exploring the basis of T2DM susceptibility from these mixed populations.…”
Section: Tcf7l2 Polymorphisms and Type 2 Diabetes Riskmentioning
confidence: 99%